Corpi globali La prostituzione in Italia - Garosi, Eleonora (Studi e saggi, 2008)
Corpi globali addresses the recent phenomenon of the proliferation of sexual services on payment, from street-walking, more visible and "disturbing", to the secluded world of top escorts, and comprising the broad range of services offered through computer technologies. The practice of sexual relations on payment has become widespread, every year involving millions of clients belonging to all social classes. This appears to be a reflection of a broader cultural model that conveys an image of sexuality divorced from affection and sentiment, which can be bought and sold like any other commodity. Which dimensions structure and supply the offer of bodies on sale? What are the reasons that induce people to purchase depersonalised and commercialised sexual services? The authors analyse the prostitution market in Italy, focusing attention on the entities that compose it, from the independent prostitutes to those who are subjected to exploitation and the criminals involved in the traffic. Reflecting on the link between demand and supply, the book offers an updated picture of the most significant changes that have taken place in the "world" of prostitution over the last decade.